EFFORTS TO MAXIMIZE THE MUSHOLLA FOR CHILDREN'S PERSONALITY DEVELOPMENT THROUGH RECITATION OF THE QURAN - Ahmad Luthfi Hidayat; Husnul Khotimah (International Conference on Social and Islamic Studies, 2021)
Islam is a religion that is considered perfect, because most aspects of human life according to them have been regulated in Islamic teachings. Overall, Islamic teachings contain several major aspects. These aspects include aspects of worship, aspects of mu’amalah, and moral aspects. These three aspects are part of what is always practiced in the daily life of Muslim. Related to moral aspects, Islamic teachings place great emphasis on Muslims to imitate the behavior of the prophet Muhammad. This is following what the prophet said, that the prophet was sent by Allah among the goals is to perfect human morals. To practice morals as taught by the prophet Muhammad saw, many ulama make efforts in the form of continuous guidance to the community, especially among children as the next generation of Muslims. The development of children is carried out in various ways and methods according to the child's growth period. One of the methods of developing children is through education and teaching. Education and teaching to children is usually carried out through religious activities held in musholla. Musholla is a place of worship in the Muslim community and is often used as a place to teach the values of kindness to Muslim children. Through this musholla, children are taught the Quran which aims to develop the personality of children. Through this research, we will explain how to maximize the musholla for the development of the personality of children through teaching the Quran. This research was conducted using a qualitative descriptive method.